Polariton Dispersion of Ferroelectric Super Lattices at Various Temperatures - Malarkodi, A.; Joseph Wilson*, K.S. (Asian Journal of Chemistry, 2013)
The variation of the optical parameters such as the static dielectric constant, high frequency dielectric constant, transverse optical phonon frequency and longitudinal optical phonon frequency are studied for the ferroelectric materials like LiNbO3 and LiTaO3 at various temperatures. Hence the behaviour of phonon polaritons at these temperatures is discussed. It is found that when the temperature increases the dispersion shifts to new values. The polaritonic gap, within which no electromagnetic radiation can pass through, is almost same at all the temperatures except at the transition region. It is extended to LiNbO3/LiTaO3 superlattices. The behaviour of various modes of the phonon polariton dispersion is investigated systematically.